Spatial and temporal assessment of drought susceptible areas in Malaysia - Othman, Melawani (2018)
Extreme events associated with climate leave Malaysia in a devastating state, which caused economic losses in the agricultural and social aspects. Upon these kinds of events, this study aims to assess the spatial distribution of areas that are prone to face drought occurrence by conjoining the meteorological and agricultural drought assessment using Standardized Precipitation Index (SPI) and Normalized Differentiation Vegetation Index (NDVI) respectively. By application of a data reduction method, the rainfall patterns of spatial and temporal rainfall distribution was defined in Malaysia. The assessment employed 180 rainfall stations in Malaysia for 35 years, from 1980 to 2014, along with 16-day composite satellite imagery, from 2001 to 2014, in order to identify spatial and temporal pattern of drought conditions in Malaysia. The meteorological drought detection employed different time lapses, and a 3-month lag was found to be the most suitable combination with the NDVI for agricultural drought detection. An interpolation method was applied for the spatial presentation of the results, and Southwest Peninsular Malaysia has demonstrated a high consistency of drought occurrence in the past. There were occurrences of severe drought along the north coast area, while Sabah and Sarawak recorded only small areas of severely dry events. During the assessment, it was also observed that SPI share strong resemblance to the dry value recorded by the oceanic indices. This strongly supports the theory that Peninsular Malaysia was highly affected by the ocean’s activities, since Malaysia itself is situated between two oceans. The combination of SPI and NDVI indicates that there are large areas in Peninsular Malaysia that are highly susceptible to events of water deficit, especially along the northwest coast area, starting from the northern peninsular, to the southern part. The middle of Peninsular Malaysia also recorded low to moderately susceptible to drought occurrence, and there are formations of high susceptibility areas in the southeast coast area. Sabah and Sarawak, however, record low numbers of areas that are susceptible, and more than half of Borneo Island is considered to as unsusceptible to drought occurrence. In a nutshell, the use of SPI and NDVI independently helps to project the historical drought events that have occurred previously, and this historical data is useful in predicting future occurrence, since most climatic events are recurrent, and have distinctive patterns that can be investigated using past events.